Analysis of Students Creative Thinking Abilities Through Project-Based Learning in Environmental Knowledge Courses - Haswan, Haswan; Ridzal, Dewi Asriani; Rosnawati, Veni (Jurnal Pijar Mipa, 2024)
The competency of creative thinking for students is very important in the era of global competition because of the level of complexity. This is because creative thinking skills are included in the six competencies that must be possessed in competition in the 21st century. This is because creative thinking skills are included in the six competencies that must be possessed in facing competition in the 21st century. Project-based learning is one method that can be used to train and improve students' creative thinking skills. This research aims to analyze students' critical thinking abilities through a project-based learning model in environmental knowledge courses. The method used in this research is descriptive. The research subjects consisted of 38 participants. The instrument used in this research is an essay test, and four indicators of creative thinking skills are considered: fluency thinking, flexible thinking, original thinking, and elaboration ability. The data analysis technique used is descriptive. The research results show that students' creative thinking abilities in environmental knowledge courses are in the high (creative) category, with a total score for all indicators is 74,75. It indicates that project-based learning is an effective strategy adapted to train and improve students' creative thinking abilities. Project-based learning is an innovative student-centered learning method where students can work autonomously to construct their learning. This is thought to cause students' creative thinking ability scores in environmental knowledge courses to be in the high category.